2017
DOI: 10.1016/j.addbeh.2017.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Cannabis use patterns and motives: A comparison of younger, middle-aged, and older medical cannabis dispensary patients

Abstract: Introduction Medical cannabis is increasingly being used for a variety of health conditions as more states implement legislation permitting medical use of cannabis. Little is known about medical cannabis use patterns and motives among adults across the lifespan. Methods The present study examined data collected at a medical cannabis dispensary in San Francisco, California. Participants included 217 medical cannabis patients who were grouped into age-defined cohorts (younger: 18–30, middle-aged: 31–50, and ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
62
3
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 121 publications
(74 citation statements)
references
References 48 publications
8
62
3
1
Order By: Relevance
“…Even though few in number, the existing studies clearly show a trend of adult rodents perceiving the effects Δ 9 -THC as more aversive than adolescents (Schramm-Sapyta et al 2007;Quinn et al 2008;Pandolfo et al 2009). Cannabis use and the development of cannabis use disorder are more frequent in adolescent users relative to middle-aged and older adults (Haug et al 2017). Thus, it would be reasonable to assess the relation between the aforedescribed trend, observed in preclinical studies, with human behavior more in depth.…”
Section: Sex and Agementioning
confidence: 99%
“…Even though few in number, the existing studies clearly show a trend of adult rodents perceiving the effects Δ 9 -THC as more aversive than adolescents (Schramm-Sapyta et al 2007;Quinn et al 2008;Pandolfo et al 2009). Cannabis use and the development of cannabis use disorder are more frequent in adolescent users relative to middle-aged and older adults (Haug et al 2017). Thus, it would be reasonable to assess the relation between the aforedescribed trend, observed in preclinical studies, with human behavior more in depth.…”
Section: Sex and Agementioning
confidence: 99%
“…In states with unrestrictive MMLs (generally states with earlier-passed MMLs), the possibility that medical authorizations were obtained for recreational use is supported by the greater similarity of some medical users to recreational users than to a medically ill population ( Harris et al , 2000 ; Haug et al , 2017 ; Reinarman et al , 2011 ; Walsh et al , 2013 ), and because many medical users used illicit cannabis before their medical authorization ( O'Connell and Bou-Matar, 2007 ). However, two reports on medical marijuana users among adult NSDUH participants provide more representative information.…”
Section: Medical and Recreational Marijuana Lawsmentioning
confidence: 99%
“…Only one study among 12th graders showed a positive association between past year illicit and prescription drug use/misuse and MCP status [37]. This might be due the fact that the MCP group consists of both medical and recreational cannabis users with a greater proportion of recreational users among younger adult MCP [38]. Therefore, the protective effect of medical motivations for cannabis use does not necessarily translate into a protective effect of MCP status within a population of young adults.…”
Section: Discussionmentioning
confidence: 99%